2015
DOI: 10.1021/cs5016035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrolyte Composition and pH on Platinum Electrochemical and/or Chemical Dissolution in Aqueous Acidic Media

Abstract: Comprehension of the impact of electrolyte nature and concentration on Pt degradation is essential for the improvement of durability of catalyst layers (CLs), which are the heart of polymer electrolyte membrane fuel cells (PEMFCs). Electrochemical and chemical dissolution of polycrystalline Pt in aqueous CF 3 SO 3 H, H 2 SO 4 , and HClO 4 solutions of different concentrations (c = 0.1 and 0.5 M) upon potential switching and holding in the 0.60−1.20 V versus RHE range is analyzed using inductively coupled plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 46 publications
8
83
0
1
Order By: Relevance
“…25 Both groups concluded that Pt dissolution from either polycrystalline Pt or Pt/C only occurs when the upper potential limit of cycling is ≥1.1 V and that dissolution occurs and dominates during the negative-going potential sweep when the upper potential limit is ≥1.3 V. A more recent study from Cherevko et al found an onset potential of 1.05-1.1 V for Pt dissolution from poly-Pt in 0.1 M HClO 4 . 26 The rotating disk electrode/on-line ICP-MS experiments on Pt single crystals and Pt/C of Lopes et al show Pt dissolution exclusively during the negative-going potential sweep when the upper potential limit of cycling is ≥1.05 V. 27 Fuyura et al 99 found that Pt dissolution during a square wave between 0.6 to 1.2 V was not affected by the identity of the acid for sulfuric, perchloric, and trifluorosulfonic acid, but was pH dependent, increasing with decreasing pH. From the pH dependence of Pt dissolution and by comparison with Pt dissolution in alkaline solution, they concluded that Pt 2+ can be formed through anodic dissolution of PtO, but not through the direct anodic dissolution of Pt to Pt 2+ .…”
Section: Journal Of the Electrochemical Society 165 (6) F3178-f3190 mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Both groups concluded that Pt dissolution from either polycrystalline Pt or Pt/C only occurs when the upper potential limit of cycling is ≥1.1 V and that dissolution occurs and dominates during the negative-going potential sweep when the upper potential limit is ≥1.3 V. A more recent study from Cherevko et al found an onset potential of 1.05-1.1 V for Pt dissolution from poly-Pt in 0.1 M HClO 4 . 26 The rotating disk electrode/on-line ICP-MS experiments on Pt single crystals and Pt/C of Lopes et al show Pt dissolution exclusively during the negative-going potential sweep when the upper potential limit of cycling is ≥1.05 V. 27 Fuyura et al 99 found that Pt dissolution during a square wave between 0.6 to 1.2 V was not affected by the identity of the acid for sulfuric, perchloric, and trifluorosulfonic acid, but was pH dependent, increasing with decreasing pH. From the pH dependence of Pt dissolution and by comparison with Pt dissolution in alkaline solution, they concluded that Pt 2+ can be formed through anodic dissolution of PtO, but not through the direct anodic dissolution of Pt to Pt 2+ .…”
Section: Journal Of the Electrochemical Society 165 (6) F3178-f3190 mentioning
confidence: 99%
“…These conclusions were based on the pH dependence of dissolved Pt observed in Pourbaix diagrams, but the authors conceded that equilibrium conditions are not achieved during the fast potential cycling used in their study. 99 Based on a correlation of difference in anodic and cathodic charges with Pt consumption rates, Mitsushima et al proposed that Pt 4+ is formed via Pt→Pt 4+ + 4e − during symmetric cycling conditions to ≥1.5 V and that cathodic formation of Pt 2+ is the predominant mechanism under slow cathodic sweep rate conditions. 50 Postulated Pt dissolution reactions and dissolved species formed under potential cycling conditions.-As discussed above, numerous dissolution reactions have been proposed to explain the dissolution behavior of poly-Pt and Pt/C.…”
Section: Journal Of the Electrochemical Society 165 (6) F3178-f3190 mentioning
confidence: 99%
“…However, it is known that typical operational conditions such as high temperature, high potential, low pH and, in particular, extensive potential cycling lead to unacceptable rates of Pt dissolution [10][11][12]. The kinetics of Pt dissolution in turn is correlated with loss of catalyst material, transformation of porous composite structure, decrease of active surface area, change in wettability of pore walls, decline of electrochemical performance, and ultimately the lifetime reduction of the device [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent detailed experimental study, Furuya et al [12] examined the influence of electrolyte composition and pH on Pt dissolution. Analysis of potential Electronic supplementary material The online version of this article (doi:10.1007/s12678-016-0313-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation